Decreased melanocortin‐4 receptor function conferred by an infrequent variant at the human melanocortin receptor accessory protein 2 gene. Issue 9 (30th July 2016) - Schonnop, Laura; Kleinau, Gunnar; Herrfurth, Nikolas; Volckmar, Anna‐Lena; Cetindag, Cigdem; Müller, Anne; Peters, Triinu; Herpertz, Stephan; Antel, Jochen; Hebebrand, Johannes; Biebermann, Heike; Hinney, Anke
Abstract : Objective: The melanocortin receptor accessory protein 2 (MRAP2) is relevant for weight regulation in mice and humans. This function is likely mediated by regulation of the melanocortin‐4 receptor (MC4R). Functional implications of human MRAP2 mutations have not been described yet. Methods: A mutation screen was conducted in MRAP2 in 184 children and adolescents with (extreme) obesity and in 184 lean controls. Detected nonsynonymous variants were genotyped in larger independent study groups (300 people with obesity and 436 individuals with normal weight). The influence of mutant MRAP2 on MC4R signaling was analyzed in vitro . Results: (1) Three (two novel) nonsynonymous MRAP2 variants were detected: p.Ala137Thr, p.Gln174Arg, p.Arg125His (rs115655382), two synonymous variants, and three intronic variants. (2) The impact of MRAP2 on MC4R function was dependent on the ratio between the two co‐expressed proteins. Increased MC4R signaling was detected at MRAP2/MC4R ratios of 2 + 1 and above. (3) The function of MC4R was reduced with the infrequent allele at the MRAP2 p.Gln174Arg variant. (4) The three nonsynonymous mutations were each only detected once among the 484 people with obesity and not among 620 individuals with normal weight. Conclusions: This was the first study describing an effect of a MRAP2 mutation on MC4R function.